The contribution of GIS in predicting impact assessment : towards managing urban planning sustainably - Asmawi, M. Zainora; Abdullah, Muhammad Faris; Abdullah, Alias; Shahbudin, Muhamad Nur Azraei (2012)
Recent movement in GIS technology advancement has great influence to the environmental and urban planning around the globe. This papers aims to discuss the establishment of a GIS-based technology as a planning tool in assisting local planning authority. The approach applied was extensively relied on baseline data, models, spatial and statistical analysis, establishing a prototype GIS system in predicting future environmental impacts. In addition, the methodology used a pragmatic technique of ‘what if’ scenario as it can assist charting possible complicated linkages between criteria from multiple sources. The system consists of some selected key components of environment, ranging from water, floodplain to geological elements. The results of the study demonstrate the strengths and ability of GIS as a powerful planning decision support tool in urban planning to create a sustainable living environment. Consequently, it also carries the value of incorporating the complexity of wicked problems existed in urban planning into a technology-based device. The outcome of this prototype GIS system can facilitate local planning authority in predicting the possible development impacts to the ambient surrounding. This is very practical to determine the sustainability of urban areas, taking into the consideration the challenges that we face today. Keywords: GIS, environment, urban planning, local planning authority.